(untitled) (Economic and Political Thought, 2018)
Ayn Rand is a popular philosopher and political thinker in the United States. Political thought researchers commonly rank her concepts in the doctrines of radical liberalism or libertarianism, though Rand herself avoided all distinctions throughout her life. Rand created her own philosophical school, which she called Objectivism. The school based its philosophy on four values: truth, happiness, reason and justice. These values also became the basis of Rand’s social and political concepts. The purpose of this article is to show how Rand understood the value of happiness and the virtue of productivity. The philosophical origins of this concept as well as its practical implementation are indicated. Happiness and productivity are ideas that have largely influenced Rand’s and her followers’ anthropological individualism, political minarchism and economic laissez-faire.